Becoming a physical education teacher: Preservice teachers’ meaning-making process in the transition between a subject didactics course and the practicum - Westerlund, Runa (Teaching and teacher education, 2023)
Research has shown that a critical teaching perspective is at risk if preservice teachers perceive a gap between university- and field-based courses. This study explores how preservice physical education (PE) teachers make meaning out of their participation in a subject didactics course and the practicum. Interviews conducted across 1 year revealed that preservice teachers experienced PE teaching as practical skills and the advocacy of movement and health during the university-based course but not during the practicum. In both contexts, teaching as didactic and embodied knowledge was perceived as being meaningful. The study suggests that emotional learning occasions, role models, and clear purposes are supportive for a critical teaching perspective.